First record of the alien bamboo leafhopper, Branchana xanthota, in Japan (Hemiptera: Cicadellidae: Deltocephalinae) - Kamitani, Satoshi (Zootaxa, 2018)
An alien bamboo leafhopper, Branchana xanthota Li, is recorded from Japan for the first time. Three species of bamboos are recognized as host plants: Phyllostachys bambusoides, Phyllostachys edulis and Pleioblastus simonii.